PENYEIMBANGAN LINTASAN PRODUKSI VULKANISIR BAN DENGAN METODE LARGE CANDIDATE RULE (LCR) - Diana Khairani Sofyan; Syarifuddin Syarifuddin; Sri Meutia; Islamiyati Islamiyati (Universitas Teuku Umar, 2019)
CV. Barona Vulkanisir Ban is a company engaged in tire remanufacturing, which is made to order. The problem that occurs in the company is that there are several divisions of unbalanced workload, in the production process at work stations. So that production is not carried out properly, there is a buildup of materials at several work stations. To solve this problem a line balancing process is carried out. The line balancing process is carried out using the Largest Candidate Rule (LCR) method, with the aim of obtaining a good trajectory balance design, to increase production efficiency and provide an overview of the different conditions of work stations before and after trajectory balancing. The results show that the method the best trajectory balance design with trajectory efficiency results of 58%, balace delay of 42%, smoothing index 156.58 minutes and work stations numbering 3. These results are certainly better than the previous conditions, where the track efficiency level is 21.74%, balance delay 78.26 % and smoothing index 463.58 minutes.